2016
DOI: 10.1128/mbio.01721-16
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Coronavirus Macrodomain Promotes Virulence and Suppresses the Innate Immune Response during Severe Acute Respiratory Syndrome Coronavirus Infection

Abstract: ADP-ribosylation is a common posttranslational modification that may have antiviral properties and impact innate immunity. To regulate this activity, macrodomain proteins enzymatically remove covalently attached ADP-ribose from protein targets. All members of the Coronavirinae, a subfamily of positive-sense RNA viruses, contain a highly conserved macrodomain within nonstructural protein 3 (nsp3). However, its function or targets during infection remain unknown. We identified several macrodomain mutations that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
333
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(345 citation statements)
references
References 56 publications
(95 reference statements)
12
333
0
Order By: Relevance
“…Our group has shown that the X domain (Mac1) is dispensable for RNA replication in the context of a SARS-CoV replicon (Kusov et al, 2015). Recently, evidence accumulated showing that the X domain plays a role in counteracting the host innate immune response (Eriksson et al, 2008;Kuri et al, 2011;Fehr et al, , 2016.…”
Section: Macrodomain I (Mac1 X Domain)mentioning
confidence: 99%
“…Our group has shown that the X domain (Mac1) is dispensable for RNA replication in the context of a SARS-CoV replicon (Kusov et al, 2015). Recently, evidence accumulated showing that the X domain plays a role in counteracting the host innate immune response (Eriksson et al, 2008;Kuri et al, 2011;Fehr et al, , 2016.…”
Section: Macrodomain I (Mac1 X Domain)mentioning
confidence: 99%
“…Some macrodomains have also evolved enzymatic activity and are capable of hydrolysing ADP‐ribosylation (see below) . As a consequence, macrodomain‐containing proteins are involved in a diverse set of cellular functions, such as chromatin remodelling and DNA‐damage repair, oxidative stress response, metabolic processes and pathogenic mechanisms . In addition to macrodomain, several other widely distributed domains have been described as readers for ADP‐ribosylation, such as the PAR‐binding zinc finger (PBZ) , the WWE (named after three of its conserved residues) , the oligonucleotide/oligosaccharide‐binding (OB) domain and the PAR‐binding motifs (PBM) which is abundant in DNA‐damage repair proteins .…”
Section: Adpr‐binding Domainsmentioning
confidence: 99%
“…In coronaviruses, the MacroD‐type macrodomain is a part of the multidomain nonstructural protein 3 (nsP3). It has been shown that this macrodomain promotes virulence and suppresses the innate immune response during severe acute respiratory syndrome (SARS) coronavirus infection . In addition to the MacroD‐type of macrodomains, a highly diverged macrodomain SUD‐M was found as a part of the nsP3 in SARS coronaviruses.…”
Section: Adp‐ribosylation In Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an ADP-ribose-1'-phosphate phosphatase mutant of the nsp3 Macrodomain of murine coronavirus MHV-A59 showed reduced replication in the liver and impaired development of liver pathology by inhibiting the expression of inflammatory cytokines [23]. The viral nsp3 Macrodomain of Severe Acute Respiratory Syndrome (SARS) coronavirus has been demonstrated to modulate and to facilitate escape from the immune response [24]. Again, a Macrodomain mutant that interferes with ADP-ribose-1'-phosphate phosphatase activity showed increased sensitivity to the IFNα-mediated antiviral response [25].…”
mentioning
confidence: 99%